2020
DOI: 10.1177/0883911520939986
|View full text |Cite
|
Sign up to set email alerts
|

A facile chemical cross-linking approach toward the fabrication of a sustainable porous ulvan scaffold

Abstract: Ulvans represent one of the most abundant marine-derived macromolecular sulfated polysaccharides accounting for numerous biological applications including in one of the fastest growing field of biomedical sciences. Tissue engineering based on biologically inspired and naturally derived polymers has been one of the prime focuses of regenerative medicine. The present investigation is intended to explore an ionic cross-linking approach at higher pH lead by the calcium ions for casting cell growth promoting scaffo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 51 publications
3
2
1
Order By: Relevance
“…Similar observation was previously reported by Madany et al [11], who attributed that to the heavily branched structure of ulvan because of its indistinct backbone. Similar observation was also reported by Gajaria et al [70] and attributed that to the presence of junction zones, where cross-linking occurs. Moreover, Madany et al [11] reported that the ulvan's disordered conformational structure, which is caused by its heterogeneous chemical composition, accounts for the presence of amorphous regions.…”
Section: Ulvan Yield and Characterizationsupporting
confidence: 89%
See 2 more Smart Citations
“…Similar observation was previously reported by Madany et al [11], who attributed that to the heavily branched structure of ulvan because of its indistinct backbone. Similar observation was also reported by Gajaria et al [70] and attributed that to the presence of junction zones, where cross-linking occurs. Moreover, Madany et al [11] reported that the ulvan's disordered conformational structure, which is caused by its heterogeneous chemical composition, accounts for the presence of amorphous regions.…”
Section: Ulvan Yield and Characterizationsupporting
confidence: 89%
“…Thus, the EDX analysis (Figure 11d) confirmed a sulfated polysaccharide with considerable protein content. The C-content in the extracted ulvan from the Egyptian Ulva fasciata in this study is lower than that reported for Indian Ulva fasciata [70], while the S content is higher. The protein content was calculated according to Alves et al [7] by multiplying the N-content by the factor 6.25, which revealed a protein content of approximately 19.06%.…”
Section: Ulvan Yield and Characterizationcontrasting
confidence: 88%
See 1 more Smart Citation
“…The genus Ulva is adapted to various environmental conditions and could be wild-harvested or cultivated regarding ulvan extraction [41][42][43]. The extraction of the polymer occurs from many different locations around the world, including the species: U. rotundata [44], U. armoricana [44,45], U. rigida [46,47], U. clathrata [48], U. fasciata [49][50][51][52], U. intestinalis [53], U. ohnoi [54,55], U. lactuca [56][57][58], U. pertusa [59], and many others. Despite the dominance of red and brown seaweed production, the particular interest of Ulva is due to its fast growth rates and high ulvan carbohydrate content [40,60].…”
Section: Ulvanmentioning
confidence: 99%
“…Ulvan is sulfated polysaccharides extracted from the green algae with more diverse and complex structures, as well as biological activities less studied in compared to other sulfated polysaccharides [ 141 , 142 , 143 , 144 , 145 , 146 ]. Up to now, the diverse forms of carriers using ulvan including nanofibers, membranes, particles, hydrogels, and 3D porous structures have been developed ( Figure 2 ) for delivery drugs, for peptide/protein [ 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 ], for wound dressing or bone tissue engineering [ 147 , 148 , 149 , 150 , 151 , 155 , 156 , 157 , 158 , 159 ], for inhibiting HeLa [ 160 ] and glioblastoma cells [ 161 ], for proliferation splenocyte [ 162 ], for enhancing fibroblasts growth and angiogenesis [ 163 ], for enhancing differentiation PC-12 cells [ 164 ], and for proliferation mesenchymal stem cells [ 165 ].…”
Section: Medicinementioning
confidence: 99%